2016
DOI: 10.47102/annals-acadmedsg.v45n11p495
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Concerns of Diabetic Patients towards Bariatric Surgery as Treatment of Diabetes

Abstract: Introduction: Bariatric surgery is increasingly recognised as an effective treatment for type 2 diabetes that significantly improves glycaemic control, even achieving remission. This study examined perceptions and concerns of diabetic patients towards bariatric surgery as a treatment option for diabetes. Materials and Methods: A total of 150 patients were recruited from a specialised diabetic outpatient clinic and completed a questionnaire (items were rated on a Likert scale from slightly important [lowest sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
2
3
1
Order By: Relevance
“…However, in contrast to others [25,42] in the present study, patients treated with metformin were more likely than others to agree that bariatric surgery will change their nutritional habits, change their life style and they will achieve their ideal weight one year after bariatric surgery while in other studies, patients treated with insulin were more interested to undergo bariatric surgery. This might be attributed to lower compliance of patients on oral therapy than those on insulin therapy.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…However, in contrast to others [25,42] in the present study, patients treated with metformin were more likely than others to agree that bariatric surgery will change their nutritional habits, change their life style and they will achieve their ideal weight one year after bariatric surgery while in other studies, patients treated with insulin were more interested to undergo bariatric surgery. This might be attributed to lower compliance of patients on oral therapy than those on insulin therapy.…”
Section: Discussioncontrasting
confidence: 97%
“…In the present study and in accordance with others [25], more educated patients were more likely to have positive attitude towards effectiveness of bariatric surgery in management of their blood glucose, mostly because they are more understandable of the bariatric surgery and complications from diabetes mellitus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Given the invasive nature of bariatric surgery, it is critical to identify patients who can best benefit from surgery. Because by using the most metabolically effective procedure, some diabetic patients still did not reach diabetes remission after surgery [ 30 ]. The present study found that, younger patients, with a shorter duration of diabetes, and lower preoperative FBS and Hba1c, with higher preoperative BMI, that were less likely to, took insulin therapy and were less likely to have had a family history of obesity were more likely to have achieved T2DM remission 1-year and 3 years after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%